REGULATORY-ADAPTIVE STATUS IN COMPARISON OF BISOPROLOL AND SOTALOL EFFICACY IN VENTRICULAR RHYTHM DISORDERS - V. G. Tregubov; I. Z. Shubitidze; S. G. Kanorskii; V. M. Pokrovsky (Российский кардиологический журнал)
Aim. To compare the efficacy of combinational therapy with added bisoprolol or sotalol, in patients with ventricular rhythm disorders (VRD) via the assessment of regulatory-adaptive status (RAS).Material and methods. Sixty VRD patients with II-III Bigger type or I-IV Lown, and with essential systemic hypertension II-III stages and/or coronary heart disease, were randomized to two groups. Group 1 received bisoprolol 6,4±1,8 mg daily, group 2 — sotalol 166,7±49,4 mg daily. As combinational therapy, all patients were taking lisinopril (12,5±4,1 mg daily and 14,0±4,6 mg daily, respectively). At baseline and in 6 months of combinational therapy, the following measures were done: quantitative assessment of RAS (by the test with cardiorespiratory synchronism), echocardiography, threadmill-test, 6-minute walking test, Holter blood pressure and electrocardiography monitoring, life quality assessment.Results. Sotalol less prominently decreases RAS than bisoprolol. Both equally improved structural and functional condition of the heart, increased exercise tolerance, showed comparable hypotensive and antiarrhythmic effects. Sotalol, comparing to bisoprolol, improved life quality more significantly.Conclusion. In VRD patients with essential systemic hypertension and/or coronary heart diease, combinational therapy with sotalol, comparing to bisoprolol, might be more preferrable due to less negative influence on RAS.